Cost-effectiveness analysis of the nonavalent human papillomavirus vaccine for the prevention of cervical cancer in Singapore. Issue 16 (15th April 2021) - Phua, Lee Cheng; Choi, Horace C.W.; Wu, Joseph; Jit, Mark; Low, Jeffrey; Ng, Kwong; Pearce, Fiona; Hall, Cameron; Abdul Aziz, Mohamed Ismail
Abstract: Background: The nonavalent human papillomavirus (HPV) vaccine has been shown to extend protection against oncogenic HPV types 31/33/45/52/58 (HPV-OV) not covered by the bivalent and quadrivalent HPV vaccines. Besides its clinical benefit, evidence on the economic value of the nonavalent vaccine is required to inform local vaccination strategies and funding decisions. This study evaluated the cost-effectiveness of replacing the bivalent vaccine with the nonavalent vaccine in the national school-based HPV vaccination programme in Singapore. Methods: An existing age-structured dynamic transmission model coupled with stochastic individual-based simulations was adapted to project the health and economic impact of vaccinating 13-year-old girls with two doses of the nonavalent or bivalent HPV vaccines in Singapore. Direct costs (in Singapore dollars, S$) were obtained from public healthcare institutions in Singapore, while health state utilities were sourced from the literature. Incremental cost-effectiveness ratios (ICERs) were estimated over a lifetime horizon, from a healthcare system perspective. Probabilistic sensitivity analysis was performed to obtain the ICERs and corresponding variations across variable uncertainty. Particularly, this study tested the scenarios of lifelong and 20-year vaccine-induced protection, assumed 96.0% and 22.3% cross-protection against HPV-OV by nonavalent and bivalent vaccines respectively, and fixed vaccine prices per dose at S$188 for nonavalent and S$61.50 for bivalent vaccines. Results: Compared with the bivalent vaccine, the use of the nonavalent vaccine was associated with an ICER of S$61, 629 per quality-adjusted life year gained in the base case. The result was robust across a range of plausible input values, and to assumptions regarding the duration of vaccine protection. Conclusion: Given the high ICER, the nonavalent vaccine is unlikely to represent a cost-effective option compared with the bivalent vaccine for school-based HPV vaccination of 13-year old female students in Singapore. Substantial price reductions would be required to justify its inclusion in the school-based programme in the future.